Formulation of the sustainable educational development framework (sedf) to improve migrant workforce contribution in malaysia - Sheikh Mohammad Maniruzzaman, Al Masud (2023)
Malaysia has witnessed an influx of foreign workers since independence, chiefly owing to its rapidly expanding economic opportunities. Low-skilled or unschooled migrants are prevalent in the labour market and constitute one-third of the national workforce. Excess low-skilled labour imposes immense pressure on the Malaysian economy, which reduces the probability of economic transformation through automation. Malaysia has the vision to be a high-income nation, and it needs a high ratio of skilled workers to achieve the target. Focusing on educational qualifications, skill testing, different kinds of training, and sharing knowledge, this study aimed to redesign some crucial factors in the recruitment, placement, employment and repatriation phases of foreign workers in Malaysia that would enhance sustainability. This study adopted a sequential exploratory mixed methods design, characterized by qualitative (in-depth interviews) and quantitative (face-to-face survey) data collection and analysis, respectively. In total, nine experts (qualitative phase) from different sectors in labour migration management and three hundred migrant workers (quantitative phase) in Malaysia were interviewed. For qualitative data, the analysis was done through the thematic analysis method taking assistance from the qualitative data analysis software NVIVO (version 1.6). Whereas the survey data analysis method is practised here with the help of SPSS 25. The results highlighted the need to re-evaluate the following crucial factors with some other issues –firstly in recruitment phase- establishing minimum educational qualifications, mandatory skill testing, establishing Malay learning centres in the country of origin, and ensuring compulsory pre-departure training for selected workers; secondly in deployment stage- confirming first orientation program after arrival in Malaysia; thirdly, in employment level of foreign workers- improvements in foreign workers‘ skills and expertise, and finally, in repatriation phase- providing various training programs and information about further employment, sharing success stories of reintegration. Thus the study formulated a sustainable educational development framework (SEDF) based on the findings of all phases of foreign workers in Malaysia. This re-evaluation will secure foreign workers‘ right to recruitment, deployment, employment and repatriation phases and thereby increase their sustainability. These findings have implications for reshaping policies around foreign workers‘ management and for increasing foreign workers‘ contribution to the Malaysian society and economy.